Modelling for evaluations of call center for public traffic and transport systems - Tica, Slaven; Radojičić, Valentina; Marković, Goran; Marković, Dejan (Technological and Economic Development of Economy, 2011)
This paper is dealing with functional organization of a call center based on human operator work. Due to significant fluctuations of user demands during the day and from day to day, the determination of required number of agents appears as actual giving the opportunities for efficient management. The purpose of this paper is to develop a mathematical model for optimal resource allocation in a call center in order to provide a satisfactory quality of service at all times, without having more agents than necessary. The objective is to find the best staffing levels or schedule that minimizes the daily costs while satisfying all constraints. To solve this problem, we propose here a two-level dynamic programming (DP) algorithm that determines the required staffing levels by shifts. The algorithm enables optimal allocation of available human resources such that the operation costs are reduced as much as possible. The practical sample is demonstrated in a case of a call center for public traffic and transport systems in metropolitan. The results comparison for different shifts duration is performed.